ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN PELANGGAN DI MASA PANDEMI (Studi Kasus Klinik Pusat Bekam Dan Ruqyah Pedurenan) - MUHAMMAD NUR ISHAK (Institut Bisnis Muhammadiyah Bekasi, 2021)
This study aims to determine whether the marketing strategy, marketing mix includes applied products, prices, promotions, locations, people, processes and physical evidence at the Center of Cupping and Ruqyah clinics can increase customers in the academy period. This research is a qualitative study using the phenomenological method, using interview and observation techniques to collect sample data of employees and clinic customers at the Center of Cupping and Ruqiyah Pedurenan. The results showed that the marketing strategy implemented in the midst of a pandemic at the Center for Cupping and Ruqiyah Pedurenan clinics in the form of a marketing mix that included products, prices, promotions, locations, people, processes, and the physical evidence had an impact on increasing customers during the pandemic. Cupping Center Clinic and Ruqiyah Pedurenan should maintain the best-applied marketing mix. The marketing solutions for the Center of Cupping and Ruqiyah Pedurenan clinics are already good, and it will be even better if the clinic continues to improve its marketing strategy considering that currently there are many similar cupping businesses that provide better service, and this is a spur for clinics to continue to innovate and improve quality. service and marketing.